1984
DOI: 10.1002/jhet.5570210641
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new derivatives of 4‐amino‐2,4‐dihydro‐1,2,4‐triazol‐3‐one as potential antibacterial agents

Abstract: Thirty new 2‐substituted‐4‐amino‐5‐alkyl or aryl‐2,4‐dihydro‐1,2,4‐triazol‐3‐ones and ten 2‐substituted‐5‐alkyl or aryl‐4‐(5‐nitro‐2‐furfurylidene)amino‐2,4‐dihydro‐1,2,4‐triazol‐3‐ones were synthesized and characterised by their sharp melting points, elemental analysis, ir and 1H nmr spectra. These new derivatives of 5‐nitro‐2‐furaldehyde were screened for their antibacterial activities. Most of the compounds showed good activity against one test organism, Staphylococcus aureus. For a few compounds, C.M.I. ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…1,2,4-triazoles and their derivatives are found to be associated with various biological activities such as anticonvulsant [1][2], antifungal [3][4][5], anticancer [6][7][8][9], antiinflammatory [10][11][12] and antibacterial properties [13][14][15][16]. Several compounds ( Figure 1) containing 1,2,4-triazole rings are well known as drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4-triazoles and their derivatives are found to be associated with various biological activities such as anticonvulsant [1][2], antifungal [3][4][5], anticancer [6][7][8][9], antiinflammatory [10][11][12] and antibacterial properties [13][14][15][16]. Several compounds ( Figure 1) containing 1,2,4-triazole rings are well known as drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in recent years some Schiff base derivatives of 1,2,4-triazoles and their reduced derivatives have been also found to possess pharmacological activities [20][21][22][23][24][25][26]. These biological data prompted us to synthesize some new bis-1,2,4-triazole derivatives, and in the present study, a novel series of bis-Schiff base derivatives resulting from the reaction of 4-amino-3-aryl-5-phenyl-4H-1,2,4-triazoles 3 with bis-aldehydes 1 and their corresponding reduced derivatives were synthesized and characterized by IR, 1 H-NMR, 13 C-NMR and mass spectral data.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4-triazoles and their derivatives are found to be associated with various biological activities such as anticonvulsant, [20,21] antifungal, [22][23][24] anticancer, [25][26][27][28] anti-inflammatory [29][30][31] and antibacterial properties. [32][33][34] Also, a series of 1,2,4-triazole derivatives have been patented and extensively employed in agriculture. [35] Derivatives of 1,3,4-oxadiazole have been found to possess a wide spectrum of pharmacological, medical, and biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In addition, it was reported that 1,3,4-thiadiazoles exhibit various biological activities possibly due to the presence of the =N-C-S moiety. 10 Moreover, synthesis of triazoles fused to another heterocyclic ring has attracted wide spread attention due to their diverse applications as antibacterial-, antidepressant-, antiviral-, antitumorial-and antiinflammatory agents, pesticides, herbicides dyes, lubricant and analytical reagents.…”
Section: Introductionmentioning
confidence: 99%